PEMBAGIAN PERAN DALAM PENGASUHAN ANAK (Studi Kasus Pada Generasi X dan Generasi Millenial di Kabupaten Lampung Tengah) - Winda Oktaviani; Dri Santoso; Aliyandi A. Lumbu; Afifuddin Ahmad Robbani (LPPM STAI Muhammadiyah Probolinggo, 2025)
In Islamic family law, childcare (hadhanah) is a shared responsibility that emphasizes the best interests of the child and the principle of justice. Where the responsibility for care is not only borne by the mother, but is a shared task that must be carried out. This is clearly regulated in the Qur'an, Sunnah, or in positive law in Indonesia. However, in reality, the role of the mother is more dominant in childcare, while the father mostly focuses on meeting economic needs. So that with this phenomenon, questions arise regarding the division of parenting roles applied by Generation X and the Millennial Generation in Central Lampung, by reviewing the factors behind the division of parenting roles, and how they are in accordance with the principles of Islamic family law. This type of research is field research on Generation X and the Millennial Generation in four sub-districts in Central Lampung Regency. This research is descriptive, with data collection techniques, namely observation, interviews, and documentation. Data analysis uses an inductive thinking framework. The results of the study show that Generation X still tends to use traditional parenting, with the dominance of the mother's role in the domestic sphere. Meanwhile, the Millennial Generation is starting to show a more equal pattern, with increased involvement of fathers in parenting, although there are some families that still use the mother's domestic role. Differences in child care are influenced by several factors, namely, changes in social and cultural, economic and educational, residential environment, and special conditions/situations. A review of Islamic law shows that flexibility in parenting roles is justified as long as it is based on the principles of justice, responsibility, and protection of children. This study emphasizes the need for a contextual understanding of Islamic family law so that it can be applied adaptively in the dynamics of modern families.